Elizabeth Kenny: the inspiration of caring - María Luz Fernández Fernández; Raquel López Maza (Universidad de Alicante, 2012)
The figure of the nurse Elizabeth Kenny has been notably recognized in all studies related to poliomyelitis, since her therapeutic methods generated a great controversy with the medical community at that time. The nursing care procedures developed by Ms. Kenny in people suffering poliomyelitis have been the objective of several research works. Those works were focused on her as a therapist, but they hardly highlighted her role as a nurse. This is a fact that remains clear in the few papers on her figure from this point of view. This topic is of a great importance since the work performed by nurses is not often appreciated outside their own professional field, as it was the case for F. Nightingale. Ms. Kenny's work is well known and recognized in medicine and physiotherapy. In this way it is important to notice that it was Ms. Kenny's experience as a nurse what allowed her to introduce some pioneer care procedures that improved the outcome of people affected by poliomyelitis. In this study, we analyze the significance and repercussion of the work done by Elizabeth Kenny in the nursing care field.